Pendekatan Manajemen Konflik sebagai Upaya Menjadi Problem Solver - Shinta Ages Putri Ariyanto (Lembaga Institute Development of Social Economic Cociety, 2026)
This study analyzes the conflict management approach as an effort to become a problem solver by viewing conflict as a structural and interactional reality in social and organizational contexts. Conflict is understood to arise from structural inequalities, differences in interests, and the dynamics of interaction, and is often not managed systematically, thus having a negative impact. The research uses a qualitative approach with a case study design through in-depth interviews, participatory observation, and documentation studies. Data analysis is carried out thematically through reduction and categorization of meaning. The results of the study indicate that conflict requires problem-solving-based management, participatory dialogue, and contextual understanding. This study emphasizes the importance of the role of actors and processes in conflict resolution and recommends the development of policies and further research in a broader context.